Bibliography Professor E.V. Rtveladze as a Source of Historical Science - T.D. Bayturaev (Researchparks Publishing, 2022)
The article examines scientific auxiliary bibliographic indexes for scientific publications in the form of books, an article by one of the major specialists in the history and archeology of the Central Asian region, academician of the Academy of Sciences of Uzbekistan, Doctor of History. prof. Edward Vasilyevich Rtveladze. The author of the article, analyzing the personal bibliographic indexes of this author, approached this issue from the point of view of searching, selecting the publication by the reader's address, by territorial principle and by language. The article also analyzes the selection and placement of the main scientific works in the bibliographic index by type of publication, which can provide a large scientific material for researchers, and scientists on issues of the region and the whole world.